The Lubb and the Learning: A Hermeneutic Correlation of the Qur’anic Ulul Albab Concept and Pedagogical Deep Learning for Holistic Intelligence - Sutarjo, Sutarjo; Iskandar Mirza (Journal of Science and Education (JSE), 2026)
This study addresses the persistent gap between traditional Islamic education, often critiqued for rote memorization, and the modern pedagogical imperative for holistic student intelligence. The purpose of this hermeneutic inquiry is to establish a correlational framework between the Qur’anic concept of Ulul Albab (QS. Ali-Imran: 190-191) and the contemporary pedagogical model of Deep Learning. Utilizing a qualitative library research method grounded in Fazlur Rahman's double movement hermeneutics, the study analyzes foundational texts in Islamic exegesis and modern educational theory. The results reveal a profound correlation: the Ulul Albab’s core characteristics of Dhikr (remembrance) align with Mindful Learning; Fikr (contemplation) correlates with Meaningful Learning; and Amal Salih (purposeful action) mirrors Joyful Learning. This synthesis provides an indigenous, Tawhidic-based pedagogical model that integrates spiritual, cognitive, and affective domains, offering a transformative framework for developing holistic intelligence (Insan Kamil) within Islamic educational institutions.